2013
DOI: 10.1007/s10278-013-9595-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Computed Tomography Protocols: Limitations of a Methodology Employing a Phantom with Location-Known Opacities

Abstract: This study aimed to determine if phantom-based methodologies for optimization of hepatic lesion detection with computed tomography (CT) require randomization of lesion placement and inclusion of normal images. A phantom containing fixed opacities of varying size (diameters, 2.4, 4.8, and 9.5 mm) was scanned at various exposure and slice thickness settings. Two image sets were compared: All images in the first image set contained opacities with known location; the second image set contained images with opacitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Previous research indicated that variation in subjective evaluation results mainly depends on observer expertise. Therefore, five junior QA testers and three experienced medical imaging QA professionals were invited to form volunteer and expert groups for comparison.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research indicated that variation in subjective evaluation results mainly depends on observer expertise. Therefore, five junior QA testers and three experienced medical imaging QA professionals were invited to form volunteer and expert groups for comparison.…”
Section: Methodsmentioning
confidence: 99%